2011
DOI: 10.1002/erv.1103
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship between Coping Strategies and Binge Eating in Nonclinical Adolescents

Abstract: The aims of the study were to determine the rate of binge eating and examine the relationship between binge eating and coping in nonclinical adolescents. A total of 1913 adolescents completed the Bulimic Investigatory Test, Edinburgh, the Adolescent Coping Scale (ACS), the Youth Self-Report and additional questions regarding the binge-eating episodes. Of the total sample, 6.94% reported bingeing in the last 6 months. The adolescents who binge eat reported a more frequent use of Intropunitive avoidance and Intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
2
1
0
Order By: Relevance
“…Our finding of a positive association between escape-avoidance coping and binge eating is similar to previous findings of a population-based study on escape-avoidance coping among individuals with current or past DSM-IV eating disorders, including AN, BN, a combination of AN and BN, or eating disorders not otherwise specified (EDNOS) (Ghaderi & Scott, 2000) and findings from studies with community adolescent samples on escape-avoidance coping and binge eating (Sierra Baigrie, 2008; Sierra-Baigrie, Lemos-Giráldez, Paino, & Fonseca-Pedrero, 2012). Evidence suggests that escape-avoidance coping serves as a short-term stress relief by immediately disconnecting individuals from the stressful situation (Aldao et al, 2010; Connor-Smith & Flachsbart, 2007).…”
Section: Discussionsupporting
confidence: 88%
“…Our finding of a positive association between escape-avoidance coping and binge eating is similar to previous findings of a population-based study on escape-avoidance coping among individuals with current or past DSM-IV eating disorders, including AN, BN, a combination of AN and BN, or eating disorders not otherwise specified (EDNOS) (Ghaderi & Scott, 2000) and findings from studies with community adolescent samples on escape-avoidance coping and binge eating (Sierra Baigrie, 2008; Sierra-Baigrie, Lemos-Giráldez, Paino, & Fonseca-Pedrero, 2012). Evidence suggests that escape-avoidance coping serves as a short-term stress relief by immediately disconnecting individuals from the stressful situation (Aldao et al, 2010; Connor-Smith & Flachsbart, 2007).…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with previous empirical evidence that supports the conceptualization of binge eating as a method of coping with negative emotional states [32][33][34]; our study found that for the sample overall, there was both a direct effect of anxiety and an indirect effect of cognitive avoidance, supporting an interpretation of partial mediation. The results from this study are novel, given that to date, many of the studies supporting this theory have extrapolated support for the role of avoidance in their examination of negative emotionality and binge eating behavior [10,27,35,36]; direct tests of the association of cognitive avoidance and binge eating have been less common [37,38].…”
Section: Discussionsupporting
confidence: 90%
“…of these, one was carried out with males (garcía-grau, Fusté, Miró, saldaña & Bados, 2004), only three address the age range from 13 to 18 years, (Hasking, 2006;sierra & lemos, 2008;sierra-Baigrie, lemos-giráldez, paino & Fonseca-pedrero, 2012) and all except two (pamies & Quiles, 2012;sierraBaigrie et al, 2012) are based on relatively small samples, analyzing a maximum of 417 participants (Fryer, Waller & Kroese, 1997;garcía-grau, Fusté, Miró, saldaña & Bados, 2002;Hernández-cortés & londoño, 2013;sim & Zeman, 2006;Halvarsson-edlund, sjödén & lunner, 2008;Huon et al, 1999). Moreover, we have not found any studies that analyze possible differences in coping and vulnerability to eating disorders in relation to age.…”
Section: Introductionmentioning
confidence: 99%